Effects of Grinding Corn through a 2-, 3-, or 4-High Roller Mill on Milling Characteristics, and Commercial Finishing Pig Growth Performance and Carcass Characteristics - J. T. Gebhardt; K. F. Coble; M. D. Tokach; J. M. DeRouchey; R. D. Goodband; J. C. Woodworth; C. R. Stark; C. K. Jones; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 922 pigs [PIC TR4 × (FAST Large white × PIC Landrace), initially 88.3 lb] were used in a 97-d experiment to determine the effects of grinding corn through various roller mill configurations on milling characteristics as well as growth performance and carcass characteristics of finishing pigs in a commercial setting. Pens were randomly allotted to 1 of 4 experimental treatments by initial BW with 11 pens per treatment and 21 pigs per pen. All diets were fed in 5 phases with the same corn-soybean meal-based diets containing 20% dried distiller’s grains with solubles. Experimental treatments included: (1) corn ground to 685μm using 2 sets of rolls (2-high); (2) corn ground to 577μm using 3 sets of rolls (3-high); (3) corn ground to 360μm using 4 sets of rolls in a fine grind configuration (4-high fine); and (4) corn ground to 466μm using 4 sets of rolls in a coarse grind configuration (4-high coarse). The same roller mill was used for all configurations with the appropriate lower rolls completely open when using 2 or 3 sets of rolls. Grinding rate (tons per hour) was greatest (P<0.05) for the 2-high and 4-high coarse configurations, followed by the 3-high configuration and lowest for the 4-high fine configuration. Electricity cost was lowest (P<0.05) per ton of ground corn for the 2-high configuration, and was greatest for the 4-high fine configuration. Pigs fed diets containing corn ground with the 2-high configuration had the greatest (P<0.05) ADFI and ADG, and pigs fed diets with corn ground using the 4-high fine configuration had the poorest ADFI and ADG. Pigs fed diets with corn ground using the 3-high or 4-high coarse configuration were intermediate. There were no differences (P>0.05) in F/G, caloric efficiency, or carcass characteristics among pigs fed diets ground with different roller mill configurations. Feed cost/lb of gain was lowest (P<0.05) for the 4-high coarse configuration and revenue/pig was greatest (P<0.05) for the 2-high and 4-high coarse configurations. Income over feed cost (IOFC) was lowest (P<0.05) for pigs fed diets with corn ground using the 4-high fine configuration; however, there were no differences (P>0.05) in IOFC among the other milling configurations. In our study, roller mill configuration had a significant impact on grinding electricity cost as well as grinding rate. However, when particle size was reduced from 685 μm to 360 μm, ADFI and ADG decreased, and there was no improvement in feed efficiency. Therefore, our study did not indicate a benefit in feed efficiency or economic return of finishing pigs when corn particle size was reduced below 685μm by grinding through a roller mill in the commercial setting in this experiment.
Keywords: finishing pigs; grinding cost; particle size; roller mill